9th International Congress of the Brazilian Geophysical Society &Amp; EXPOGEF, Salvador, Bahia, Brazil, 11-14 September 2005 2005
DOI: 10.1190/sbgf2005-448
|View full text |Cite
|
Sign up to set email alerts
|

Terdiurnal tides in MLT region over Cachoeira Paulista (22.7° S; 45° W)

Abstract: Five years of winds measurements obtained by a SkiYmet meteor radar at Cachoeira Paulista (22.7 • S, 45.0 • W) are used to investigate the terdiurnal tide. This type of tide is frequently observed in the meteor region but the mechanisms responsible for its production are not yet completely explained. Among the possible causes are solar direct forcing and nonlinear interactions between the diurnal and semidiurnal tides. Nonlinear interaction between diurnal and semidiurnal tides can generate two secondary waves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…[2009] reported that at low latitudes the maximum amplitudes of the terdiurnal tide are seen during equinoxes, with a primary peak in March and a secondary peak in October. A similar result was obtained at a low‐latitude Southern Hemisphere station at Cachoeira Paulista, Brazil (22.7°S, 45°W), where the maximum of the terdiurnal tide occurs during equinoxes (mainly during February‐March) [ Batista et al , 2004; Tokumoto et al , 2007]. Based on wind measurements by a High‐Resolution Doppler Interferometer (HRDI) housed on the Upper Atmosphere Research Satellite (UARS), Smith [2000] found that the maximum amplitudes at midlatitudes occur during winter and fall equinox.…”
Section: Introductionsupporting
confidence: 60%
“…[2009] reported that at low latitudes the maximum amplitudes of the terdiurnal tide are seen during equinoxes, with a primary peak in March and a secondary peak in October. A similar result was obtained at a low‐latitude Southern Hemisphere station at Cachoeira Paulista, Brazil (22.7°S, 45°W), where the maximum of the terdiurnal tide occurs during equinoxes (mainly during February‐March) [ Batista et al , 2004; Tokumoto et al , 2007]. Based on wind measurements by a High‐Resolution Doppler Interferometer (HRDI) housed on the Upper Atmosphere Research Satellite (UARS), Smith [2000] found that the maximum amplitudes at midlatitudes occur during winter and fall equinox.…”
Section: Introductionsupporting
confidence: 60%
“…and latent heat release. Seasonal and interannual variability of the most dominant tides, i.e., diurnal, semidiurnal and terdiurnal in the middle atmosphere, have been studied with the help of models and observations by various investigators for the last couple of decades over the globe (Forbes, 1982;Vial et al, 1991;Tokumoto et al, 2007;Guharay and Franke, 2011;Guharay et al, 2013a). In general the semidiurnal tide is stronger than the diurnal tide at high latitude and at tropical latitude the diurnal tide predominates.…”
Section: Introductionmentioning
confidence: 98%
“…Apparent AO with maximum amplitude in autumn, in winter and autumn, as well as in winter and spring mainly at high latitude (e.g., Esrange, 68°N, 21°E), higher midlatitude (e.g., Eaton, UK, 52.6°N, 2.2°W), and lower midlatitude (e.g., Garchy, 47°N, 3°E; Montpazier, 44°N, 1°E; London, Canada, 43°N, 81°W) stations was demonstrated in the preceding investigations [e.g., Thayaparan , ; Smith , ; Younger et al , ; Aso , ; Beldon et al , ; Jiang et al , ]. By contrast, at the low‐latitude stations (e.g., Cachoeira Paulista, 22.7°S, 45°W; Maui, 20.75°N, 156.43°W), prominent SAO with maxima near equinoxes was found [ Batista et al , ; Tokumoto et al , ]. Near the equator (e.g., Koto Tabang, 0.2°S, 100.3°E; Triunelveli, 8.7°N, 77.8°E; and Pameungpeuk, 7.4°N, 107.4°E), both AO and SAO were shown in terdiurnal components [ Venkateswara Rao et al , ; Yue et al , ].…”
Section: Introductionmentioning
confidence: 99%